Penerapan DeLone and McLean Model untuk Mengukur Kesuksesan Aplikasi Akademik Mahasiswa Berbasis Mobile - Ernawati, Muji; Heni Hermaliani, Eni; Nur Sulistyowati, Daning (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2020)
MyUBSI Student application is a mobile-based academic application used by students university of Bina Sarana Informatika to obtain academic information. during the implementation of the application, has never been done an analysis of the success of the application . This research aims to know what factors affect the success of MyUBSI Student application using DeLone and McLean Model. The variables used in this research are system quality, information quality, service quality, use, user satisfaction, trust and net benefits. The population of this research is active students of Bina Sarana Informatika University with the number of samples used as many as 78 students. Data collection techniques using questionnaires, and for the data analysis techniques used are inferential statistics. Based on the results of research, of the 12 hypotheses there are 5 hypotheses received i.e. information quality has a positive and significant influence on use, information quality has a positive and significant influence on trust, the quality of the system has a positive and significant influence on user satisfaction, use has a positive and significant influence on the net benefit, and user satisfaction has a positive and significant influence on the net benefits.